Pembuktian Anggapan Analisa Geoteknik (Pergerakan Tanah) Menggunakan Model Fizikal - Che Nen, Akhtarul Norfaiza (Universiti Sains Malaysia, 2006)
A number of tests were conducted on physical models to verify various phenomena associated with soil movements in geotechnical engineering. Generally, the purpose was to observe movement and sliding surfaces during geotechnical processes. The load test on a model soil showed that soils settlement is having a higher magnitude in the middle right below the loading. Thus, the higher stress has resulted in greater settlement. The result partly verifies the ‘stress bulb’ but in way of observing settlement. The same test however failed to show the lateral sliding movement. A second experiment has resulted in angle of repose determined during the test. Angle of repose is important for construction works. Loose and dense soil grain distribution inside the material can also be observed. The overall result however failed to show any clear movement of soil during failure either in passive or active Rankine state. To improve the performance of the tests, the model should be larger than already constructed and period of observation should also be larger, say at least a month.